1995
DOI: 10.1007/bf00329798
|View full text |Cite
|
Sign up to set email alerts
|

Egg shell quality, clutch size and hatching success of the great tit (Parus major) and the pied flycatcher (Ficedula hypoleuca) in an air pollution gradient

Abstract: Egg shell thickness, egg volume, clutch size and hatching success of Parus major and Ficedula hypoleuca were studied at 14 study sites around a copper smelter complex in Harjavalta, south-west Finland, in 1991-1993. In 1991-1992 unhatched eggs were collected to measure shell quality. F. hypoleuca was more susceptible to pollutants than P. major, the response of which was weaker in all aspects studied. Egg shells of F. hypoleuca were about 17% thinner and eggs were about 8% smaller in volume near the factory th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
87
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 45 publications
5
87
1
Order By: Relevance
“…All data except Mg were log-transformed to meet normality assumptions. The upper matrix represents the r-values of the correlation; the bottom matrix shows the associated p-values Laboratory and field studies suggest that metals like mercury, lead, copper, and aluminum impair eggshell formation and cause eggshell thinning (Stoewsand et al 1971;Lundholm and Mathson 1986;Lundholm 1991;Eeva and Lehikoinen 1995). The observed reduction of eggshell thickness at the contaminated site (up to 17% in some nests) is similar to that described for other areas contaminated with high concentrations of heavy metals in Finland (Eeva and Lehikoinen 1995) and acidified areas in Norway (Nybo et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…All data except Mg were log-transformed to meet normality assumptions. The upper matrix represents the r-values of the correlation; the bottom matrix shows the associated p-values Laboratory and field studies suggest that metals like mercury, lead, copper, and aluminum impair eggshell formation and cause eggshell thinning (Stoewsand et al 1971;Lundholm and Mathson 1986;Lundholm 1991;Eeva and Lehikoinen 1995). The observed reduction of eggshell thickness at the contaminated site (up to 17% in some nests) is similar to that described for other areas contaminated with high concentrations of heavy metals in Finland (Eeva and Lehikoinen 1995) and acidified areas in Norway (Nybo et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Cu has usually been found in higher concentrations than Ni or Zn throughout the food chain although Zn has been emitted more than Cu until 1992 (Table 1). Elevated heavy metal concentrations have been reported in understorey vegetation (Helmisaari et al 1995), pine (Derome and Nieminen 1998), spruce (Heliövaara and Väisänen 1991), birch (Koricheva and Haukioja 1995), insects (Heliövaara et al 1990), spiders (Koponen and Niemelä 1995), and birds (Eeva and Lehikoinen 1995) (Table 4).…”
Section: Emissions Deposition and Contaminationmentioning
confidence: 92%
“…F. hypoleuca was more susceptible to pollutants than P. major, the response of which was weaker in many aspects. The breeding success of P. major was below background levels up to 3-4 km from the smelter (Eeva and Lehikoinen 1996) whilst F. hypoleuca was affected severely only next to the smelter (ca 1 km) (Eeva andLehikoinen 1995, 1996). No clear differences in the female condition (Eeva et al 1997b), and in the density of ectoparasites in the nests (Eeva et al 1994) of these two bird species in relation to the pollution were found.…”
Section: Birdsmentioning
confidence: 99%
“…in the area more contaminated with heavy metals, compared to the pied fl ycatchers in the areas more distant from sources of pollution (Eeva, Lehikoinen, 1995). Th is diff erence in concentrations of Ca in both species of birds may be related to diff erences in their foraging behaviour.…”
Section: Resultsmentioning
confidence: 98%
“…It is known that the total amount of calcium that is transferred to an egg from the female body aff ects the clutch size, thickness and weight of the shell (Eeva, Lehikoinen, 1995). Mean concentrations of Ca in egg contents of collared fl ycatchers varied from 1255.2001 ± 3.3268 (Hetmanskyi NPP) to 1538.8370 ± 0.0510 (forest park) and in egg shells -from 430.8237 ± 4.2584 (Hetmanskyi NPP) to 655.6440 ± 11.0718 mg/kg (Vakalivshchyna).…”
Section: Resultsmentioning
confidence: 99%